Jesus: The infected healer and infectious community – Liminality and creative rituals in the Jesus community in view of COVID-19 - Dube, Zorodzai (HTS teologiese studies, 2020)
Using theories in medical anthropology, especially the ideas inspired by Hector Avalos and George Foster, the study explains three activities associated with the early Christian healthcare system: (1) touching infectious people, (2) hospitality towards possibly infectious people and (3) the practice of itinerary evangelism as an activity that earned Christianity the dubious role of being a carrier of infectious diseases. Discussed alongside the issues associated with the advent of COVID-19, the study aims at (1) reflecting that early Christian healthcare system, which was an offshoot of Jewish healthcare systems, had practices that were perceived to exacerbate infection. In addition, (2) in view of the advent of COVID-19 pandemic, although of lesser catastrophe to ancient plagues, the study proposes that such epidemics call upon the collective actions of mercy and kindness, as Jesus did towards the infected. Theoretically, Victor Turner’s concepts of liminality and communitas assist in imagining the discursive ideas concerning labelling and marginalisation of the Jesus movement, with comparative implication towards those suspected to have contracted the deadly COVID-19 virus. The study concludes with a warning against Christian practices that may further inflame infection by suggesting alternative practices for love and empathy towards others.Contribution: Using ideas concerning infectious diseases in antiquity, the study reinterprets the Jesus movement as a movement that was perceived as carriers of infectious disease. Due to fear of infectious diseases, the rituals associated with hospitality towards the outsiders, the touch and laying of hands and iternary lifestyle were seen as promoting infection. Taking this perspective, the Jesus movement whose modus operandi is mostly associated with the periphery of the villages and cities created alternative rituals for the outcast. In view of the spread of COVID19, such stance by the Jesus movement provides lessons for the church and society to reach out to people who are considered infectious and burden to main society.